Perancangan Alat Spinner Ergonomis (Study Kasus PT. Baasithu, Floating Storage and Offloading Petrostar) - Diana Chandra Dewi; Corry Handayani; Irfan Heru Prasetyoa (Jurnal INOVATOR, 2019)
Snack foods have become an integral part of people's lives. Food snacks arevery many kinds and vary widely in the form of necessities and prices. Fried is afrying process using cooking oil. Cooking oil is very closely for our health.Repeated oils can lead to degradation even in health hazards. With anappreciation of health factors, there are often complaints in PT.Baasithu clientabout oil content in processed fried foods. Given this question has actually founda solution that is by using a spinner. Small industries will not be able to reachprices that are not in accordance with the amount of production.The purpose of this design is to create an ergonomic spinner capable ofreach by small industries. The design of this tool using anthropometry theory toproduce the size of the tool in accordance with the size of the employees of PT.Baasithu. Phase completion of anthropometry data conducted on employees, bodydimensions required are: 1. Reach far, 2. Wide grip. The data will be processedwith data adequacy test, uniformity test, and percentile calculation, then do thedesign process of spinner. This ergonomic oil slicer uses a centrifugal force todrain oil. The way the processed food of fried food will be rotated in the slicer sothat the oil will be sliced and out through the hole in the slicer.